2019
DOI: 10.5021/ad.2019.31.5.545
|View full text |Cite
|
Sign up to set email alerts
|

Severe Cutaneous Adverse Reactions: A Single-Center Retrospective Study of 173 Patients in China

Abstract: Background Severe cutaneous adverse reactions (SCAR) to drugs are a crucial public health issue and the use of systemic corticosteroids in SCAR has been controversial. Objective To analyze clinical features, causative drugs, treatment, outcomes, and prognostic factors of SCAR in the case-series of 173 patients, and add more information to the debate of using systemic corticosteroids in SCAR management. Methods A retrospective study of 173 SCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…The remaining 4467 studies were screened for title, abstract, and full text, and 64 potentially relevant studies were identified. Of the 64 studies that underwent data extraction, 3 studies described the same study population and were excluded from the meta-analysis. Furthermore, there were 23 studies that did not count the SJS/TEN associations at the patient level and thus were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 4467 studies were screened for title, abstract, and full text, and 64 potentially relevant studies were identified. Of the 64 studies that underwent data extraction, 3 studies described the same study population and were excluded from the meta-analysis. Furthermore, there were 23 studies that did not count the SJS/TEN associations at the patient level and thus were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…An Indian study showed that SJS/TEN and DRESS were the most and least common, respectively [ 7 ]. In Asia, SJS/TEN appears to be the most common followed by DRESS and AGEP [ 16 , 17 ]. The predominance of DRESS in our study can be attributed to genetic differences.…”
Section: Discussionmentioning
confidence: 99%
“…Renal dysfunction related to DRESS has been reported to happen in 10% to 64% of patients and is usually attributed to AIN 2,5,7,11 . Allopurinol‐induced DRESS is more likely to suffer from renal injury than other drugs.…”
Section: Discussionmentioning
confidence: 99%
“…1,5,7,9,10 Renal dysfunction related to DRESS has been reported to happen in 10% to 64% of patients and is usually attributed to AIN. 2,5,7,11 Allopurinol-induced DRESS is more likely to suffer from renal injury than other drugs. In our study, serum creatinine elevation was seen in 71.2 % of patients, and up to 21.2% of patients underwent either short-or long-term dialysis.…”
Section: Discussionmentioning
confidence: 99%